2003
DOI: 10.1093/humrep/deg188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic studies of HLA-DRB1 alleles in patients with unexplained recurrent abortion in the Japanese population

Abstract: These findings suggest that HLA-DRB1*1502 might be a risk allele for unexplained recurrent abortion in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…In decidua, PIBF is known as a target gene of hsa-miR 520h (Supplementary Table 3), and PIBF can mediate progesterone-induced suppression of decidual lymphocyte cytotoxicity (Laskarin et al 2002). We predicted HLA-DPB1 as a target gene of hsa-miR-520f, which was low expressed in villus (Supplementary Table 3), and just as Takakuwa et al (2003) reported HLA-DPB1 might be a risk allele for unexplained recurrent abortion in the Japanese population. From target gene results (Supplementary Table 3), hsa-miR-519a-1 upregulated in the decidua of RSA patients could target 3 0 UTR of CD69; therefore, intracellular expression of CD69 in endometrial and peripheral T cells represents a useful marker in women with recurrent miscarriage (Ramhorst et al 2003).…”
Section: Discussionmentioning
confidence: 66%
“…In decidua, PIBF is known as a target gene of hsa-miR 520h (Supplementary Table 3), and PIBF can mediate progesterone-induced suppression of decidual lymphocyte cytotoxicity (Laskarin et al 2002). We predicted HLA-DPB1 as a target gene of hsa-miR-520f, which was low expressed in villus (Supplementary Table 3), and just as Takakuwa et al (2003) reported HLA-DPB1 might be a risk allele for unexplained recurrent abortion in the Japanese population. From target gene results (Supplementary Table 3), hsa-miR-519a-1 upregulated in the decidua of RSA patients could target 3 0 UTR of CD69; therefore, intracellular expression of CD69 in endometrial and peripheral T cells represents a useful marker in women with recurrent miscarriage (Ramhorst et al 2003).…”
Section: Discussionmentioning
confidence: 66%
“…Another possible factor capable of enhancement of fgl2 activity might be decreased HO expression observed in invasive trophoblast, syncytiotrophoblast and endothelial cells of decidual vessels of patients with spontaneous abortion [185]. The most important reason for altered Th1/Th2 balance in cases of recurrent miscarriage is not precisely known, however, reduced expression of HLA-G isoforms on trophoblast or relationship between high production of Th1 cytokines and certain genotypes could provide some explanation [186,187,188,189,190,191]. Recently, the size of a microsatellite polymorphism of HO-1 gene has been found to correlate with RA [192].…”
Section: Cytokines Of Th1/th2 Activity Indoleamine 23 Dioxygenase Amentioning
confidence: 99%
“…Recurrent spontaneous abortion (RSA) 3 is usually defined as the loss of Ն3 consecutive pregnancies at Ͻ20 weeks of pregnancy (1 ). Among the risk factors for RSA [chromosomal (2 ), genetic (3 ), anatomical (4 ), endocrinological (5 ), and placental anomalies (6 ); infection (7 ); and stress (8 )], thrombophilic conditions attributable to venous thromboembolism, as in the case of antiphospholipidantibody syndrome (APS) (9 -12 ), have a relevant role.…”
mentioning
confidence: 99%